2006
DOI: 10.1303/aez.2006.99
|View full text |Cite
|
Sign up to set email alerts
|

Visual 'pinpoint' location associated with pheromonal cue in males of the black chafer Holotrichia loochooana loochooana (Coleoptera: Scarabaeidae)

Abstract: Females of the black chafer Holotrichia loochooana loochooana (Sawada) (Coleoptera: Scarabaeidae) release anthranilic acid, which functions as sex attractant pheromone for males and aggregation pheromone for females. When a white lure treated with anthranilic acid was placed next to an untreated black lure in the field, males were observed to make pinpoint landings significantly more frequently on the latter. When the distance between the two lures was increased from 0 to 20 cm, frequency of pinpoint landing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
1
8
1
Order By: Relevance
“…D. ishigakiensis males are often observed to land on a female or very close to her before mating in the field (Arakaki et al, 2004). The importance of visual orientation has been demonstrated in the black chafer (Fukaya et al, 2006). These observations suggest that visual stimuli may be involved in the mating behavior of D. ishigakiensis; however, the results of the present study indicated that a visual target is not necessary to capture males with pheromone-baited traps.…”
Section: Discussioncontrasting
confidence: 55%
“…D. ishigakiensis males are often observed to land on a female or very close to her before mating in the field (Arakaki et al, 2004). The importance of visual orientation has been demonstrated in the black chafer (Fukaya et al, 2006). These observations suggest that visual stimuli may be involved in the mating behavior of D. ishigakiensis; however, the results of the present study indicated that a visual target is not necessary to capture males with pheromone-baited traps.…”
Section: Discussioncontrasting
confidence: 55%
“…6) or at a 5-cm interval at right angle to the wind (Fukaya et al, 2006), the males were observed to land equally on the two lures. This suggests that a female releasing a maximum amount of pheromone (hereafter, major female) would have an equal chance to attract a male when she takes a position near another major female.…”
Section: Discussionmentioning
confidence: 92%
“…The anthranilic acid attracts males , and causes them to land directly on a black or dark object, such as a female. In the process, the males switch orientation cues from olfactory to visual when they are around 15 to 20 cm from the pheromone source (Fukaya et al, 2004(Fukaya et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hidaka (1972) reported the necessity of visual stimuli in addition to pheromones to attract Hyphantria cunea (Drury) (Lepidoptera: Arctiidae) males, and Carlton and Cardé (1990) noticed that Lymantria dispar (L.) (Lepidoptera: Lymantridae) males also used visual cues after landing on females. More recently, Fukaya et al (2006) demonstrated the importance of visual stimulus (black and gray sources) in combination with the female sex pheromone anthranilic acid for mate location in the black chafer, Holotrichia loochooana loochooana (Coleoptera: Scarabaeidae). Our results show that C. sordidus relies exclusively on olfactory cues.…”
Section: Discussionmentioning
confidence: 99%